2013
DOI: 10.2967/jnumed.112.107995
|View full text |Cite
|
Sign up to set email alerts
|

18F-FPEB, a PET Radiopharmaceutical for Quantifying Metabotropic Glutamate 5 Receptors: A First-in-Human Study of Radiochemical Safety, Biokinetics, and Radiation Dosimetry

Abstract: Identification of safe and valid PET radioligands for metabotropic glutamate receptor, type 5 (mGluR5), is essential to measure changes in brain mGluR5 in neuropsychiatric disorders, to confirm central mGluR5 occupancy of drug candidates, and to guide dose selection for obtaining an optimum therapeutic window. Here we present the results of a first-inhuman study assessing the safety and effectiveness of a novel PET radiopharmaceutical, 18 F-3-fluoro-5-[(pyridin-3-yl)ethynyl] benzonitrile ( 18 F-FPEB), for quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
102
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 38 publications
5
102
2
Order By: Relevance
“…This pattern is similar to the one reported in humans by Wong et al but slower than in monkeys (5,18). The detection of only 1 polar radiometabolite by Hamill et al, however, could suggest that the radiometabolite eluting directly before the parent fraction (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This pattern is similar to the one reported in humans by Wong et al but slower than in monkeys (5,18). The detection of only 1 polar radiometabolite by Hamill et al, however, could suggest that the radiometabolite eluting directly before the parent fraction (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Acknowledging this situation, Wong et al optimized the cumbersome and low productive radiosynthesis of 18 F-FPEB (3-18 F-fluoro-5-(2-pyridinylethynyl)benzonitrile) by simplifying the process and increasing the radioactive yield. They additionally performed an in vivo distribution study in humans, which confirmed the previously described pharmacokinetics (5). Recent preliminary preclinical evaluation of 18 F-FPEB has shown promising results, but a thorough validation for preclinical use has not been reported yet (6).…”
mentioning
confidence: 48%
“…The highly selective mGlu 5 allosteric radioligand [ 18 F]FPEB binds to an allosteric site on mGlu 5 that is occupied by the prototypical mGlu 5 NAM, 2-methyl-6-(phenylethynyl)pyridine hydrochloride (MPEP), and is being used to assess mGlu 5 occupancy in multiple clinical studies Russell, 2014;Wang et al, 2007;Wong et al, 2013). It is clear that allosteric modulators can bind to multiple topographically distinct allosteric sites on mGlu 5 Gregory et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1) and the rapid metabolism of O-arylcarbamates compounds (i.e., CURB/URB694) where half of the parent compound is metabolized in the first 20 m after injection (8). The gallbladder timeactivity curve is not uniformly reported in other dosimetry papers but is not unique to 11 C-CURB (18,19). The large variance in gallbladder uptake of radioactivity observed is attributed to variable hepatobiliary clearance and gallbladder emptying among the subjects.…”
Section: Discussionmentioning
confidence: 92%